2020
DOI: 10.3389/fpsyg.2020.01717
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Early Scientific Thinking Through Curiosity

Abstract: Curiosity and curiosity-driven questioning are important for developing scientific thinking and more general interest and motivation to pursue scientific questions. Curiosity has been operationalized as preference for uncertainty (Jirout and Klahr, 2012), and engaging in inquiry-an essential part of scientific reasoning-generates high levels of uncertainty (Metz, 2004; van Schijndel et al., 2018). This perspective piece begins by discussing mechanisms through which curiosity can support learning and motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 64 publications
1
40
0
7
Order By: Relevance
“…The results of this study are in line with the opinion outlined by (J. J. Jirout, 2020) that curiosity can encourage motivation to carry out scientific investigations through the process of scientific thinking. Scientific thinking is a knowledge-seeking activity that involves searching for information starting from asking questions, formulating hypotheses, making predictions, determining variables, making observations, collecting data, and making conclusions (Jirout & Zimmerman, 2015).…”
Section: Resultssupporting
confidence: 90%
“…The results of this study are in line with the opinion outlined by (J. J. Jirout, 2020) that curiosity can encourage motivation to carry out scientific investigations through the process of scientific thinking. Scientific thinking is a knowledge-seeking activity that involves searching for information starting from asking questions, formulating hypotheses, making predictions, determining variables, making observations, collecting data, and making conclusions (Jirout & Zimmerman, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Promoting students’ curiosity to learn in educational contexts could make learning more enjoyable and support motivation ( Midgley et al, 2001 ), which could support future learning ( Jirout et al, in review ), and it also could positively influence learning behaviors, such as question asking and class participation ( D. Park et al, 2017 ; Jirout and Klahr, 2020 ). This might be especially important and effective for domains like science ( Jirout, 2020 ), where children’s ability to ask and think about questions is seen as fundamental, with the inclusion of question asking as the first of eight scientific and engineering practices that span across all grade levels and content areas in the National Research Council’s National Science Education Standards ( NRC, 2012 ). Although the current test only looked at math instruction, we were still surprised not to have observed a single instance of teachers prompting students to generate questions, which could be an important way to help them recognize things they might be curious to know.…”
Section: Discussionmentioning
confidence: 99%
“…Information seeking behavior is driven and motivated by individual awareness of the difference between current and target uncertain states (Gottlieb et al, 2013 ; Van de Cruys et al, 2021 ). Previous studies have shown that curiosity levels may be affected or suppressed when individuals are uncomfortable with uncertainty or believe that they have a high probability of failure (Hulme et al, 2013 ; Jirout, 2020 ). Therefore, exploratory behavior that stems from the expectation of acquiring information and interest in new experiences can be better realized in low-risk contexts.…”
Section: Risk Assessment and Psychological Characteristicsmentioning
confidence: 99%